2015
DOI: 10.1590/0103-8478cr20140734
|View full text |Cite
|
Sign up to set email alerts
|

Carrapatos (Acari: Ixodidae) em mamíferos silvestres do Parque Nacional da Serra da Canastra e arredores, Minas Gerais, Brasil

Abstract: O presente estudo relata ixodídeos em mamíferos silvestres no Parque Nacional da Serra da Canastra e arredores, no estado de Minas Gerais, Brasil. De julho de 2005 a junho de 2014, foram coletadas 58 larvas, 133 ninfas e 43 carrapatos adultos em 40 eventos de captura de mamíferos de vida livre do Parque e arredores. Nos hospedeiros da ordem Carnivora, foram identificados Amblyomma ovale Koch, 1844, Amblyomma sculptum Berlese, 1888, Amblyomma tigrinum Koch, 1844, Dermacentor nitens Neumann, 1897 e Rhipicephalus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Similar results were found when investigating ticks from wild carnivores (Lycalopex vetulus, Cerdocyon thous, Chrysocyon brachyurus and Puma concolor) in the Brazilian Cerrado, where A. sculptum represented 98.6% of the total number of sampled ticks, mainly in the nymphal stage [44]. The present study is also in agreement with other studies carried out in several regions of Brazil, which also indicated a strong association between A. sculptum nymphs and wild carnivores [29,45,46]. Amblyomma sculptum is a generalist species, widely distributed in the Brazilian biomes of Cerrado, Pantanal, and degraded areas of the Atlantic forest [44,[47][48][49][50].…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were found when investigating ticks from wild carnivores (Lycalopex vetulus, Cerdocyon thous, Chrysocyon brachyurus and Puma concolor) in the Brazilian Cerrado, where A. sculptum represented 98.6% of the total number of sampled ticks, mainly in the nymphal stage [44]. The present study is also in agreement with other studies carried out in several regions of Brazil, which also indicated a strong association between A. sculptum nymphs and wild carnivores [29,45,46]. Amblyomma sculptum is a generalist species, widely distributed in the Brazilian biomes of Cerrado, Pantanal, and degraded areas of the Atlantic forest [44,[47][48][49][50].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, their parasitism by ticks and the diseases caused by agents that ticks transmit among hosts are largely unknown. There are a few records in Brazil of ticks parasitizing Neotropical otters (Lontra longicaudis) in the states of Paraná, São Paulo, Minas Gerais and Santa Catarina (Arzua et al, 2005;Labruna et al, 2005;Martins et al, 2015;Verdin et al, 2015), in the Atlantic Rainforest and Cerrado ecoregions. However, until we know, there is just one study reporting the presence of a single tick on a giant otter caught in the Balbina hydroelectric reservoir, in the Brazilian Amazon region (Rosas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%